2020
DOI: 10.1523/eneuro.0355-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Co-Regulation of Locomotor Development and Motor Neuron Synaptogenesis is Uncoupled by Hypoxia in Zebrafish

Abstract: Hypoxic injury to the developing human brain is a complication of premature birth and is associated with longterm impairments of motor function. Disruptions of axon and synaptic connectivity have been linked to developmental hypoxia, but the fundamental mechanisms impacting motor function from altered connectivity are poorly understood. We investigated the effects of hypoxia on locomotor development in zebrafish. We found that developmental hypoxia resulted in decreased spontaneous swimming behavior in larva, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…We followed the previously established hypoxia protocols (Stevenson et al, 2012;Xing et al, 2015;Son et al, 2020). Briefly, embryonic zebrafish were placed in a sealed Plexiglass chamber connected via a controller that monitored and adjusted nitrogen gas flow to a desired 1% pO 2 set point in an incubator (set as 28 • C) (Figure 1A).…”
Section: Hypoxia Reagents and Hypoxia Recoverymentioning
confidence: 99%
See 4 more Smart Citations
“…We followed the previously established hypoxia protocols (Stevenson et al, 2012;Xing et al, 2015;Son et al, 2020). Briefly, embryonic zebrafish were placed in a sealed Plexiglass chamber connected via a controller that monitored and adjusted nitrogen gas flow to a desired 1% pO 2 set point in an incubator (set as 28 • C) (Figure 1A).…”
Section: Hypoxia Reagents and Hypoxia Recoverymentioning
confidence: 99%
“…Briefly, embryonic zebrafish were placed in a sealed Plexiglass chamber connected via a controller that monitored and adjusted nitrogen gas flow to a desired 1% pO 2 set point in an incubator (set as 28 • C) (Figure 1A). Previous work had demonstrated that 1% of pO2 hypoxia is non-lethal (Stevenson et al, 2012;Son et al, 2020). Since the equilibration of oxygen partial pressure in water could take several hours, we pre-equilibrated all solutions for at least 4 h before use.…”
Section: Hypoxia Reagents and Hypoxia Recoverymentioning
confidence: 99%
See 3 more Smart Citations